MODERN TECHNOLOGIES OF VITAMIN AND MINERAL COMPLEXES PRODUCTION - I.A. Gromov; R.M. Torshkhoeva (Union of pediatricians of Russia, 2008)
The article highlights the information on the technology of the vitamin and mineral complexes production, actions to ensure not only high quality production but also safety for the staff and environmental protection.Key words: vitamin and mineral complexes, production technologies.